PENGARUH KRISIS EKONOMI AMERIKA TERHADAP PASAR MODAL INDONESIA DILIHAT DARI ANALISIS LAPORAN KEUANGAN PERUSAHAAN - Rosetianie Kautsar Ashshofia; Tina Sulistiyani (Universitas Ahmad Dahlan, 2011)
This study aims to determine whether there are significant differences in the performance of mining companies listed in Indonesia Stock Exchange prior to and during the U.S. economic crisis seen from the analysis of financial statements of companies in 2004-2009. The population in this study were 22 mining companies. Using a purposive sampling technique obtained 10 samples of mining companies. The analysis tools kormogrov-smirnov to test normality of data, paired sample t-test to test normal distribution of data. Wilcoxon test to examine the data distribution is not normal. The ratio shows a significant difference before the economic crisis America during the year 2004-2006 and the American economic crisis of 2007-2009 is the solvency ratio and the ratio of the activity. Ratio showed no significant differences before the economic crisis America during the year 2004-2006 and the U.S. economic crisis in 2007-2009 is the liquidity ratio, profitability ratios and market ratios.